Determinants of Social Commerce Acceptance in Saudi Arabia: Moderating Role of Customer Gender, Age, And Experience - Abdulrahman ANDIJANI; Kyeong KANG (Communications of International Proceedings, 2022)
Research motivation- The previous decade witnessed that Information and Communication Technology (ICT) brings the digital revolution to every corner of human life. Particularly, the service industry has largely shifted from a brick-and-mortar format to an online. In this respect, a revolution in Social Commerce (s-commerce) brought more automated and faster services. Although middle eastern countries had tremendous potential to expand their online businesses through s-commerce, there is scant literature on the factors that influence the low acceptance of s-commerce. To examine the antecedents of s-commerce acceptance, this research employed the Unified Theory of Acceptance and Use of Technology (UTUAT2), expanded by social commerce constructs and user trust. Moreover, by drawing on individual difference literature, this study examines customer gender, age, and use experience as moderates on UTUAT2 factors and purchase intention relationships. Research design/methodology- After establishing the reliability and validity of measurement scales, the final model was tested with 596 valid responses in structural equation modeling (SEM) based on partial least squares (PLS) in Smart-PLS 4 software. Main findings- The results illustrate that performance expectancy, facilitating conditions, price value, and habit are positively and significantly related to customer purchase intention. We also found that social commerce constructs and user trust positively relate to customer purchase intentions. The findings of this research show that customers' gender, age, and experience moderate the effects of facilitating conditions, price value, hedonic motivation, and habit on purchase intentions and use behavior. Implications-The research provides implications to businesses,  policymakers, and governments to understand the dynamics of s-commerce and devise their policies accordingly.
Keywords: UTAUT2; SCCs; customer trust; structural equation modeling; Saudi Arabia